SPECIFICS OF AGENDA SETTING IN THE ELECTORAL PERIOD - Ulia Petrovna Belenkaya (Вестник Северо-Кавказского федерального университета, 2022)
This article is devoted to the peculiarities of the formation of information agenda in the electoral period. Here are the results of various studies media agenda during elections, the specificity of the work of the journalist. Special attention is given to manipulate public opinion.